2010
DOI: 10.1007/s11164-010-0149-y
|View full text |Cite
|
Sign up to set email alerts
|

Stability of hydrogen peroxide during perhydrolysis of carboxylic acids on acidic heterogeneous catalysts

Abstract: This paper describes a study of the stability of hydrogen peroxide in the presence of different aluminosilicate materials, in connection with an investigation of carboxylic acid perhydrolysis. During the reaction, aluminosilicate materials such as H-b zeolites, mesoporous material H-MCM-41 and alumina initiate the decomposition of hydrogen peroxide. The reason of the spontaneous decomposition of H 2 O 2 is related to the partial dealumination of these zeolites. However, in the case of experiments carried out w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…As discussed previously, the enhancing effect of the MW heating was attributed to the so‐called selective heating, which produces an increase in the temperature of the aqueous phase, thus boosting the production of peracetic acid. Cation exchange resins have a similar effect upon epoxidation because they have the ability to accelerate the rate of perhydrolysis . It can be concluded that the enhancing effect of the MW heating observed previously for non‐catalytic epoxidation of oleic acid is now very much masked by the effect of the heterogeneous catalyst.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…As discussed previously, the enhancing effect of the MW heating was attributed to the so‐called selective heating, which produces an increase in the temperature of the aqueous phase, thus boosting the production of peracetic acid. Cation exchange resins have a similar effect upon epoxidation because they have the ability to accelerate the rate of perhydrolysis . It can be concluded that the enhancing effect of the MW heating observed previously for non‐catalytic epoxidation of oleic acid is now very much masked by the effect of the heterogeneous catalyst.…”
Section: Resultsmentioning
confidence: 87%
“…Cation exchange resins have a similar effect upon epoxidation because they have the ability to accelerate the rate of perhydrolysis. 50,51 It can be concluded that the enhancing effect of the MW heating observed previously for non-catalytic epoxidation of oleic acid 8 is now very much masked by the effect of the heterogeneous catalyst. The total perhydrolysis rate (r TOT ) consists of two contributions: r TOT = r HOMOG + r HETEROG .…”
Section: Microwavesmentioning
confidence: 82%
“…Moreover, in the case of Amberlite IR-120, it has been demonstrated by some authors , that cation exchange resins have the ability to accelerate the rate of perhydrolysis. Thus, it can be inferred that the enhancing effect of the MW heating observed previously for noncatalytic epoxidation is now outpaced by the effect of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…All these applications are based on the oxidative properties of these compounds, due to the chemical bond O O OH . The literature concerning the synthesis of short-chain peroxycarboxylic (3-1 carbon atoms) acid is relatively extensive with homogeneous [2][3][4][5][6][7][8][9] and heterogeneous catalysts [10][11][12][13][14][15][16][17][18]. Indeed, they are the main peroxycarboxylic acids used in industrial scale, mainly because of their high reactivity and so lower stability.…”
Section: Introductionmentioning
confidence: 99%
“…All these applications are based on the oxidative properties of these compounds, due to the chemical bond. The literature concerning the synthesis of short-chain peroxycarboxylic (3–1 carbon atoms) acid is relatively extensive with homogeneous and heterogeneous catalysts. Indeed, they are the main peroxycarboxylic acids used in industrial scale, mainly because of their high reactivity and so lower stability. On the other hand, studies of peroxycarboxylic acids with long carbon chains (higher than four carbons) are rare. , These long-chain peroxycarboxylic acids can be used, when the solubility of a short-chain peroxycarboxylic acid or hydrogen peroxide in the organic phase is limited.…”
Section: Introductionmentioning
confidence: 99%